2005
DOI: 10.1021/ac050150y
|View full text |Cite
|
Sign up to set email alerts
|

Discovery, Biosynthesis, and Structure Elucidation of Metabolites of a Doping Agent and a Direct Analogue, Tetrahydrogestrinone and Gestrinone, Using Human Hepatocytes

Abstract: Tetrahydrogestrinone (18a-homo-pregna-4,9,11-trien-17beta-ol-3-one, THG) is an anabolic androgenic steroid sold to athletes as an undetectable performance enhancer. Being an unapproved substance, no legitimate in vivo human excretion studies could be performed to identify urinary markers of this doping agent. In vitro systems were used as an alternative approach to study the human metabolism of THG and the gestrinone analogue, which is a marketed drug. Incubations of both compounds in the presence of human hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 19 publications
1
19
0
1
Order By: Relevance
“…In an excretion study with gestrinone, two unidentified gestrinone metabolites were detected as well as the parent drug as glucuronide conjugates [148,149]. Based upon the mass spectrometric data from an in-vitro study, one metabolite was identified as 18-hydroxy-gestrinone [139]. In another study 2,16␤-dihydroxygestrinone was found as the major metabolite, as well as gestrinone and 6␣-hydroxygestrinone ( Fig.…”
Section: Gestrinonementioning
confidence: 98%
See 1 more Smart Citation
“…In an excretion study with gestrinone, two unidentified gestrinone metabolites were detected as well as the parent drug as glucuronide conjugates [148,149]. Based upon the mass spectrometric data from an in-vitro study, one metabolite was identified as 18-hydroxy-gestrinone [139]. In another study 2,16␤-dihydroxygestrinone was found as the major metabolite, as well as gestrinone and 6␣-hydroxygestrinone ( Fig.…”
Section: Gestrinonementioning
confidence: 98%
“…The oral contraceptive gestrinone (13␤-ethyl-17--ethynyl-17-hydroxygona-4,9-11-trien-3-one), commonly used in the treatment of endomentriosis, is prohibited in sports and can be used in the synthesis of THG [18,135,139]. In an excretion study with gestrinone, two unidentified gestrinone metabolites were detected as well as the parent drug as glucuronide conjugates [148,149].…”
Section: Gestrinonementioning
confidence: 99%
“…AAS with conjugated double bonds, such as gestrinone [6,39] and tetrahydrogestrinone (THG) [6,40], do not undergo extensive biotransformation routes; their metabolic pathways include mainly hydroxylations at C-2, C-6, C-16 or even C-18 positions. In the case of trenbolone, metabolism process is restricted to C-17 epimerization [41].…”
Section: Proposed Metabolism Scheme For Steroids With Conjugated Doubmentioning
confidence: 99%
“…hydroxy-13,14-dehydro-17,17-dimethyl-18-nor-5␣-androst-2-eno-(2,3-c)-pyrazole 4␣-hydroxy-stanozolol39 Stenbolone(2-methyl-5␣-androst-1-ene-17␤-ol-3-one) 2-methyl-5␣-androst-1-ene-16␣-ol-3,17-dione 2-methyl-5␣-androst-1-ene-16␤-ol-3,17-dione 2-methyl-5␣-androst-1-ene-3z,16z-diol-17-one 2-methyl-5␣-androst-1-ene-3␣-ol-17-one 2-methyl-5␣-androst-1-ene-16z,17␤-ol-3-one 18-hydroxy-2-methyl-5␣-androst-1-ene-3,17-dione40 1-Testosterone (17␤-hydroxy-androst-1-ene-3-one) 5␣-dihydrotestosterone 5␣-androst-1-ene-3␣,17␤-diol 5␣-androst-1-ene-3,17-dione 5␣-androst-1-ene-3␣-ol-17-one 1-epitestosterone…”
mentioning
confidence: 99%
“…Liver fractions (2 ), hepatocyte cell cultures (3)(4)(5), and primates (6,7 ) have been used as alternatives to human administration in studies of metabolism. These alternative models are not ideal, however.…”
mentioning
confidence: 99%